Comparative Evaluation of Neck Length, Relative Neck Length and Total Body Height in Cervical Spondylosis Affected and Non-Affected Individual: Neck Length and Height in Cervical Spondylosis - Ameer, Muhammad Kamran; Mehboob, Faiza; Ahmad, Nadia; Moeed, Khalida; Ahmed, Hira; Irshad, Faiza (Pakistan Journal of Health Sciences, 2024)
Anthropometric measurements, including neck length, relative neck length and total body height, have been proposed as potential indicators of cervical spine health, yet their association with cervical spondylosis remains relatively understudied. Objective: To compare neck length, relative neck length, and total body height between individuals affected by cervical spondylosis and a non-affected control group. Methods: This case-control study was conducted at Department of Anatomy Multan Medical and Dental College (MMDC), Multan from April 2023 to September 2023. Cases were diagnosed with cervical spondylosis and controls were selected from the same population without a history of cervical spine pathology or symptoms. The collected data were analyzed using IBM SPSS, version 27.0. Results: Gender distribution revealed females in both cases (63, 60.6%) and controls (59, 56.7%). The age of participants ranged from 25 to 75 years. The mean age for cases was 49.2 ± 12.93 years and for controls was 49.7 ± 13.19 years. The mean neck length among cases and controls was 105.2 ± 17.22 mm and 107.7 ± 20.02 mm, respectively. Regarding relative neck length, cases and controls exhibited measurements of 6.41 ± 1.07 mm and 6.42 ± 1.27 mm, respectively. Height-wise, cases measured 164.4 ± 10.27 cm, while controls measured 168.3 ± 8.53 cm. Conclusions: In conclusion, while no significant differences were observed in neck length or relative neck length between cervical spondylosis patients and controls, a notable disparity in height was noted.